A case of primary tracheal squamous cell carcinoma arising from malignant transformation of recurrent respiratory papillomatosis, with a complete response to concurrent chemoradiotherapy. (October 2021) - Kovacs, Aaron C; Vodanovich, Domagoj; Mogridge, Emily K; Wun, Lisa; Corry, June
Recurrent respiratory papillomatosis is a human papillomavirus-mediated condition characterised by the development of benign squamous papillomata of the respiratory tract. Malignant transformation of recurrent respiratory papillomatosis, while rare, carries a poor prognosis and there are limited data surrounding treatment options, particularly in inoperable disease. We present the case of a 64-year-old male who developed malignant airway obstruction secondary to primary tracheal squamous cell carcinoma in the setting of a 5-year history of recurrent laryngotracheal papillomatosis, requiring placement of tracheostomy while on veno-venous extracorporeal membranous oxygenation. He was managed with cisplatin-based definitive chemoradiotherapy and had a complete metabolic response on post-treatment positron emission tomography/computed tomography, and remains free of recurrent squamous cell carcinoma at 16 months following treatment. This case supports the use of combined chemoradiotherapy as a potential therapeutic option for patients with primary tracheal squamous cell carcinoma, and emphasises the challenges associated with the long-term management of recurrent respiratory papillomatosis.